Blast hole plug based on formaldehyde resin, system and loading method

By using a two-component mixture based on formaldehyde resin and catalyst to form a rigid foam plug during mining blasting, the problems of low sealing efficiency and noise and large particulate emissions of traditional plugs are solved, and more efficient rock breakage and lower environmental impact.

CN119317807APending Publication Date: 2025-01-14OXIQUIM SA
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202380044961.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-07
Filing Date
2023-06-05
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively seal the explosion energy during mining blasting, resulting in noise and particulate emissions, affecting the environment and operational safety, and the traditional plug material has high density and low transportation and installation efficiency.

Method used

A two-component mixture of formaldehyde-based resin and catalyst is used to form a rigid foam plug in situ. It quickly generates low-density, efficient and closed explosion energy in the blasting hole through chemical reactions, and transfers energy to rocks to reduce noise and particulate emissions. .

Benefits of technology

It significantly improves rock crushing, reduces noise and particulate emissions, reduces material transport and operating time, reduces operational and logistics costs, and ensures safe temperature control and avoids detonation line damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169649550000101
    Figure BDA0005169649550000101
  • Figure BDA0005169649550000102
    Figure BDA0005169649550000102
  • Figure BDA0005169649550000111
    Figure BDA0005169649550000111
Patent Text Reader

Abstract

A method of forming a mining blasthole plug includes loading a two-component mixture of a resin and a catalyst into a blasthole wherein the two-component mixture produces a rigid foam in situ and detonates the two-component mixture once the rigid foam cures. The invention also relates to a system for forming a mining blast plug for implementing the method; the mixture for use as a mining blast hole plug comprises a two-component mixture of a resin and a catalyst, wherein the resin is formaldehyde-based; the invention also relates to a method for loading and detonating a mining blast hole by using the two-component mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method and system for forming a plug for plugging a blast hole void by in-situ forming a rigid foam block produced from a two-component mixture of a resin and a catalyst, wherein the resin is a formaldehyde-based resin such as phenol-formaldehyde (PF) resin, urea-formaldehyde (UF) resin, melamine-formaldehyde (MF) resin, melamine-urea-formaldehyde (MUF) resin, phenol-resorcinol-formaldehyde resin (PRF), formaldehyde-based resin modified with lignin or tannin, and their derivatives. Background Art

[0002] In the mining industry, blasting is a very important part of extraction activities because the blasting results affect the economic and operating costs of the post-extraction stage.

[0003] Blasting is an operation aimed at extracting ore from a rock mass, taking advantage of the energy released by explosives placed in the blastholes formed during the drilling and blasting phases. During the blasting process, special attention is paid to maximizing rock fragmentation and its corresponding logistical, economic and energy-saving effects in subsequent operations, such as grinding the material and minimizing negative impacts. In order to achieve maximum fragmentation, different variables in the production process must be managed, such as variables such as explosive type, explosive density, charge factor, grid design and / or detonation frequency. The blasting process generates high noise and particulate matter, which may affect nearby communities and workers involved in the operation. If the noise and particulate matter limits set by environmental regulations are exceeded, mining companies will face severe environmental penalties.

[0004] The blast holes present in the mine area / section to be blasted may have different depths and diameters, typically up to 30 meters in depth (open pit) and up to an average of 45.72 centimeters (18 inches) in diameter, depending on the detonation design. The blast holes may have water or mud at the bottom. The blast holes are loaded with a suitable explosive and then sealed with material to contain the gases released during the explosion. This seal is called a plug and is usually constructed from the material left after drilling (chips or crushed stone). Because of the ease of construction (manually with a shovel or light machine) and the availability of materials, the process is carried out in this way, which produces a type of plug that can be up to half the linear height of the hole due to the weight of the plug. However, this design is not efficient in terms of containing the energy generated by the explosive, which results in noise emissions and the lifting of particulate matter.

[0005] In order to improve the results of the blasting phase, various techniques have been applied, which involve the development of different types of explosives and their location inside the blastholes, as well as the engineering and design of accessories and devices that serve as blasthole plugs, the purpose of which is to confine the explosive charge in order to exploit the energy released during the fragmentation and displacement of the rock, increase the efficiency during blasting, and therefore maximize the fragmentation of the rock during blasting. In this way, it is intended to achieve beneficial results in terms of logistics and energy savings in the operations after blasting. Summary of the invention

[0006] The present invention relates to a two-component mixture or composition comprising a catalyst and a formaldehyde-based resin, a method and system for forming a burst hole plug, and the use of said composition to carry out said method of forming a plug, thereby improving the results of currently known and used techniques.

[0007] The blasting phase begins with drilling a hole, the diameter and depth of which vary depending on the mineral type and the mine or section. Hole sizes range from 5 to 20 meters in depth and 15 to 80 centimeters in diameter. Depending on the hole depth, there may be water or mud.

[0008] Conventionally, in open pit blasting, once the holes are configured, a detonator is installed at the bottom of each hole and the explosives are loaded. Plugs or cuttings are added to the explosives (to separate them), which is equivalent to filling with drill cuttings (crushed stone) to a height of about 2 to 4 meters, in order to increase the fragmentation index. This filling can be done manually by workers with shovels, or by dump trucks filling each hole with drill cuttings. Finally, the detonation stage is carried out, which is usually done by an electronic system.

[0009] In mining operations, typically 20 to 50 holes are constructed in the pre-splitting zone associated with wall breaking, and 30 to 150 holes are constructed in the production hole zone (bank) associated with all the minerals to be processed in the crushed ore.

[0010] The purpose of constructing pre-split holes is to minimize the pressure in the hole so that cracks can be created between adjacent holes in the pre-cut line and thus reduce the pressure in the production hole, which is one of the reasons why the noise during blasting in pre-split holes is much greater than in the production hole.

[0011] During blasting, the time used to fill a conventional hole with explosives and drill cuttings can range from 3 to 10 minutes per hole, so depending on the number of holes, the process in one mission can take from 1 hour (minimum number of holes 20 x minimum time 3 minutes) to 25 hours (maximum number of holes 150 x maximum time 10 minutes).

[0012] In the present invention, once the detonator is installed and the explosive is placed, drill cuttings (as a spacer) are added, the minimum amount of drill cuttings being no more than 50 cm in height, and after the drill cuttings are added, the resin of the present invention is added to form a blasting plug. The purpose of inserting the drill cuttings into the hole includes preventing the resin of the plug of the present invention from contacting the explosive.

[0013] The invention of the present application forms the blasting plugs in a very efficient and rapid manner and has the advantage of reducing the filling time of the blasting holes to no more than 1 minute per hole. Obviously, this stage will depend on the volume and size of the holes to be filled. Thus, in normal operation, considering the operation of a maximum of 150 holes, the filling time will not exceed 2.5 hours, while the operation of conventional holes will require 25 hours. Depending on the depth of the blasting hole, there may be water or mud, but this will not affect the efficiency of forming the plug of the invention.

[0014] In the present invention, blast plugs are generated in situ by chemical reaction of a formaldehyde-based resin with a catalyst to which a swelling agent is optionally added. The mixture of resin and catalyst can be applied to a watery or muddy surface, depending on the depth of the blast hole, without affecting the performance of the plug formed. The blast plug generated in situ allows to contain the blast energy and maximize its transfer to the rock, thereby obtaining a greater degree of fragmentation, while reducing the adverse environmental impacts of noise and particulate emissions, which may affect the workers in situ and the community surrounding the mining operation.

[0015] On the other hand, the chemical reaction with the resin to form the rigid foam is usually highly exothermic, which makes it difficult to use in mining operations, since the maximum temperature specification of the detonating cord, which is related to temperature, usually does not exceed 55-60° C. Therefore, the exothermic reaction generated by the rigid foam cannot exceed the safety range of 50° C., so as not to interfere with the correct detonation of the explosives. If the detonating cord is damaged due to excessive temperature or other effects of the reaction, serious misfire problems (failure to detonate) will occur, resulting in operational damage and the need to search for the misfired explosives that constitute a danger, because the explosives must not be left in those places without detonation, but must be removed from the site, which involves additional and excessive operating costs.

[0016] Furthermore, the Good Practice Manual for Reactive Soils recommends using explosives in soils at temperatures not exceeding 55°C to avoid reaction of oxidising species present in the explosives (such as ammonium nitrate) with iron-based reactive species present in the soil.

[0017] In situ plug formation using the formaldehyde resin of the present invention produces a low energy exothermic reaction which has advantages in mining operations. DETAILED DESCRIPTION

[0018] Open-pit mining uses drill cutting plugs, a material obtained from drilling holes, which is readily available and very easy to handle. With this plug the hole is sealed, but since it has no cohesive force, the gas retention rate is low and eventually most of the cuttings are ejected from the hole collar (surface opening). In this way, the gas pressure released by the detonation is not used effectively, so the rock fragmentation is not optimal and undesirable environmental impacts occur, such as large amounts of particulate matter emissions, which not only affect the workers in the mine itself, but also the people around the mining area. In addition to the above, serious environmental impacts caused by noise are also common, both in the situ itself and in nearby communities.

[0019] To address these problems, different systems have been designed to contain the blasting gases.

[0020] For example, use the Insert tool to A plug (Dyno Nobel) is inserted into the blast hole. A plug is a device consisting of a liner filled with aggregate that is pressed using an insertion tool to keep it in place in the blast hole.

[0021] Document WO2018 / 102858 discloses a sealing plug or retaining plug for stemming a blasting hole, which includes a device formed by two elongated wedge-shaped elements made of plastic material, which are placed in the hole so that when detonated, both wedge-shaped elements apply radially opposite forces to the blasting hole wall to lock the plug in place.

[0022] Document CL201701076 discloses another example of a retaining plug for a blast hole, comprising a separation disc and a weight, the weight being integrated in the separation disc located inside the blast hole. The separation disc allows the separation between the explosive and the loaded plug or aggregate, crushed stone or debris plug to be maintained in order to seal the blast hole.

[0023] These types of mechanical devices are usually made of a high-hardness polymer material with the appropriate shape to reflect and refract the shock waves generated by the detonation, but are not very effective because they are difficult to install correctly and the pressure of the gas often causes them to pop or rupture.

[0024] Another technology that has been developed involves forming cement compositions to form blast hole plugs in order to avoid dissipation of energy generated by the explosion.

[0025] For example, US2011259228 describes an aluminosilicate geopolymer composition comprising as reactants: water; a chemical activator consisting of an alkali metal salt, an alkali metal base and mixtures thereof; and a cement-like reactive material comprising the following components: a thermally activated aluminosilicate mineral; calcium aluminate cement; and calcium sulfate. This type of cement-like product forms a plug (or block) with good cohesion and high hardness and has good gas retention. However, it is not feasible to use these materials in blasting areas because a large amount of material and heavy machinery are required to form the product, which is not feasible from a logistical point of view for mining operations because it takes time to transport large amounts of material to the blasting area.

[0026] Another technology for forming plugs or drill plugs consists of a container system that includes different components and is able to form the plug in situ. For example, document WO9514208 discloses a device that includes two bags, one bag is arranged inside the other bag, and both bags are located inside a container, which is located near the blast hole, the inner bag containing an isocyanate compound and the other bag containing a mixture of polyol resin and freon. When the inner bag is broken, the isocyanate reacts with the polyol resin and freon of the outer bag to form a rigid foam contained in the outer container, which becomes a foam plug in the drill hole. On the other hand, document ES8800739 proposes a similar mechanism for forming a perforated plug, which forms a platform at the desired height to support the explosive, allowing the formation of foam when polymerized methylene diisocyanate is mixed with polyol.

[0027] Another example of conditions for forming a rigid foam plug in situ in a blast hole is described in document CN108341919, which discloses forming a foam by reacting two polymer components (polyisocyanate and polyether polyol) and adding expandable graphite and a blowing agent, which is used to fill the blast hole.

[0028] Document US6553887 also discloses a foam formulation having the ability to seal and suppress explosions, so as to suppress the explosion wave generated by the activation of an explosive device and aerosols containing chemical and biological agents. The document specifically discloses a formulation comprising a surfactant (alkyl ether sulfate, α-olefin sulfonate and alkyl sulfosuccinate), a foam stabilizer (long-chain fatty alcohol), a polyalkylene glycol (polypropylene glycol monomethyl ether with a molecular weight of 425) and water.

[0029] On the other hand, document NL6901503 discloses the use of non-polymer compounds for forming foams, such as anionic, cationic and non-ionic soaps and surfactants and saponins and proteins, or inorganic foam formers such as colloidal aluminum oxide and aliphatic carboxylic acids or phosphoric acids or their salts, or sulfonated products of mineral oils and alcohols, and horse chestnut extracts, and document DE213902414 discloses a foam consisting of anionic synthetic moisturizers, fatty alcohols, water, alcohol-dissolving adjuvants, dispersants of film-forming synthetic materials (preferably copolymers of vinyl acetate or vinyl propionate with dialkyl maleates or ethylene, or SB copolymers), the purpose of which is to prevent the formation and ignition of dust during blasting operations.

[0030] Another technique related to the technical field of the present invention relates to the formation of gels by reacting chemical agents with water present in a blast hole to form a plug or barrier. For example, EP3132205 discloses the formation of polyacrylamide gels with water present in a blast hole, which can be used as a barrier material for loading explosives in the blast hole. Another example is RU2753652, which describes a foamed silica gel formed from sodium silicate, "nanosil-30" silicon dioxide, ABSC foaming agent, orthophosphoric acid, ferric chloride and water. The resulting gel plug can be used as a low-density plug in a blast hole when breaking up a rock mass during the extraction of solid minerals.

[0031] In addition, document WO2014201514 (CL201503656) discloses the formation of a super absorbent polymer gel column as a gelled elongated body, which is at least 25 times its own weight in water, which can improve the explosion efficiency by reducing the detonation pressure. In this document, no specific disclosure of the gel-forming agent is made, and it should be noted that the embodiment uses a super absorbent polymer (SAP) or any similar agent having the ability to absorb desalted water equal to or greater than 25 times its own weight.

[0032] Finally, document CL201503059 indicates the formation of potassium polyacrylate gels which can be used as barrier materials for explosive loading and / or as gravel plugs.

[0033] While these types of techniques form a rigid foam or absorbent gel (which may or may not be generated in situ), they suffer from the disadvantage of forming an ineffective plug because the resulting product is not sufficiently rigid to adequately retain particulate matter or reduce noise emissions from the blasting operation.

[0034] In the prior art, phenol-formaldehyde, melamine-formaldehyde and urea-formaldehyde resins are known when combined with each other to form rigid foams. However, the use of products obtained with these resins solves technical problems that are completely different from those proposed by the present invention.

[0035] For example, WO9932534 relates to a binder product for use as an adhesive in the manufacture of wood products, fiberglass products and paper laminates comprising a modified phenol-formaldehyde or melamine-formaldehyde resin based on resin solids of a cyclic urea prepolymer.

[0036] CN107556514 discloses the formation of melamine formaldehyde-based rigid foams for the production of melamine-formaldehyde foam boards modified with polytetrahydrofuran for flame retardant thermal insulation.

[0037] On the other hand, CN106832762 discloses a method for preparing a low-density flame-retardant melamine formaldehyde resin rigid foam for use as a thermal insulation material. The method requires molding and drying stages to obtain the rigid foam.

[0038] CN104448189 discloses a method for producing a rigid polyurethane foam modified with a phenolic resin, which can be used as a heat-insulating material and is waterproof, and is widely used as a heat-insulating material in urban heating pipelines, petrochemical pipelines, refrigeration equipment, and bus air conditioners. FR2248296 also discloses an insulating material formed by a rigid foam. The rigid foam is composed of a thermoplastic styrene polymer and a curable resin based on a melamine / formaldehyde condensate.

[0039] These resins have also been used in the manufacture of building materials. For example, document CN105838025 discloses a method for preparing modified rigid polyurethane foam (PIR) using melamine formaldehyde resin.

[0040] From the prior art it can be seen that formaldehyde resins (particularly phenol-formaldehyde, melamine-formaldehyde, urea-formaldehyde resins) have various applications and are combined with each other to form rigid foams, however, none of these documents discloses a foam having the properties of the present invention, nor does it suggest its application in fields such as mining blasting.

[0041] Furthermore, rigid foams based on polyurethane have the disadvantage that these materials are toxic, have high reaction temperatures, are incompatible with industrial explosives and are expensive, thus making them unsuitable for use as blasting plugs.

[0042] While most of these documents disclose the formation of rigid foams, none focus on the mining field to form blast hole plugs in situ which contain the blast energy and maximize the energy transfer to the rock, provide greater fragmentation, and thereby reduce the adverse environmental impacts of noise and particulate matter emissions.

[0043] The density of the rigid foam plays a fundamental role in the results obtained with the present invention, as low density rigid foams have been found to work better than polyurethane based rigid foams within a wider range of densities.

[0044] The advantage of having a low density reduces the amount of material that must be transported to the mining site, thus reducing the density of 0.2-0.3kg / m compared to conventional technologies 3 The rigid foam of the invention allows to move about 1 / 5 of the amount of material needed to meet the requirements, which has a favorable effect on operating and logistics costs. On the other hand, the use of a density of 0.2 to 0.3 kg / m 3 Foams of the present invention of the order of magnitude have demonstrated greater sound wave dissipation, thereby reducing decibels and reducing dust emissions during blasting. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 : Photograph showing laboratory results of a two-component mixture of resin and catalyst, where the following resins were tested in a polycarbonate tube: (1) phenolic resin: PF phenol formaldehyde at a molar ratio of 1.6; (2) PUR: polyurethane resin; (3) pMDI: polymethyl diisocyanate (4) pMDI-LS: Low-reactivity polymethyl diisocyanate (5) PRF: The molar ratio of formaldehyde resin / (resorcinol + phenol) is 0.8 to 1.0; (6) MUF-1: The molar ratio of formaldehyde resin / (melamine + urea) is 1.2 to 1.8 (low viscosity); (7) MUF-2: The molar ratio of formaldehyde resin / (melamine + urea) is 1.2 to 1.8 (high viscosity).

[0046] Figure 2 : Surface temperature measured as a function of time during the formation of the following rigid foam: Phenolic resin: PF phenol formaldehyde molar ratio of 1.6; PUR: polyurethane resin; pMDI: polymethyl diisocyanate pMDI-LS: Low Reactivity Polymethyl Diisocyanate PRF: the molar ratio of formaldehyde resin / (resorcinol+phenol) is 0.8 to 1.0; MUF-1: the molar ratio of formaldehyde resin / (melamine+urea) is 1.2 to 1.8 (low viscosity); MUF-2: the molar ratio of formaldehyde resin / (melamine+urea) is 1.2 to 1.8 (high viscosity).

[0047] Figure 3 : represents the configuration and design diagram of the blast hole compared with the conventional plug solution according to the parameters in Table 3.

[0048] Figure 4 : Flow chart of blasthole loading using the resin and catalyst mixture of the present invention.

[0049] Figure 5: Surface heat release during foaming of the present invention measured over time (seconds) at room temperature of 20°C.

[0050] Figure 6 : Photo sequence of explosions at time 0, 30 and 50 milliseconds. Upper: conventional explosion using a chip plug; Lower: explosion using a phenolic resin plug of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0052] The invention corresponds to a method for producing plugs made of rigid polymer material in blast holes previously loaded with explosives, wherein these plugs are produced in situ by chemical reaction of formaldehyde-based resins, catalysts and additives that impart different properties to the material to be used, such as density, hardness, pH value, etc. The resins are of the phenol-formaldehyde (PF), phenol-resorcinol-formaldehyde (PRF), melamine-urea-formaldehyde (MUF) and / or lignin-formaldehyde type.

[0053] The technical problem solved by the present invention has been solved in different ways in the prior art. However, the solution proposed in the present invention involving a method for in-situ formation of a plug from a formaldehyde-based resin is not disclosed in the prior art.

[0054] The in-situ formation method consists of filling the blast hole to a certain height with a reactant, the reaction taking place upon mixing, and has the advantage that the method requires a very short time to form the plug. The plug formed in situ can confine the blast energy and maximize the transfer of this energy to the rock, thereby making the rock more fragmented and greatly reducing the operating costs of the post-extraction production stage. In addition, the plug obtained by the method of the present invention has the additional advantage of reducing the adverse environmental impacts of noise and particulate emissions that affect on-site workers and the communities surrounding the mining operation.

[0055] The system ensuring the method of applying the rigid foam forming agent consists of a mixer-applicator capable of handling highly corrosive substances and homogeneously mixing the agents in the necessary and optimal concentration to form the material used as a bursting plug.

[0056] The method of constructing blasting plugs using the polymer material derived from formaldehyde and phenolic compounds of the present invention unexpectedly increases rock fragmentation by at least 25%, reduces the drop in air pressure in the monitoring system, and reduces detonation decibels and particulate matter by at least 50% compared to methods typically used in such mining operations.

[0057] It is known that phenol-formaldehyde based resins can be produced in such a way that the setting temperature and time (hardening process) are determined by the different physicochemical parameters that characterize them, such as the total solids content; pH value; the molar ratio of formaldehyde (formalina) / phenol and / or urea, melamine, resorcinol; the size and basicity of the polymers. If this resin is mixed with additives capable of generating gas during the setting process, highly porous materials (foams) can be obtained that can present different properties such as elasticity, hardness, toughness and plasticity. In addition to depending on the internal composition of the resin used, these properties can also reflect the amount and reaction speed during setting, which depends on the type, concentration and amount of catalyst added to the reaction mixture.

[0058] Additionally, other additives may be added to the formaldehyde-based resin, such as blowing agents, surfactants, fillers, buffers, or any other additives compatible with the setting characteristics required for the application. Thus, by controlling the composition of the formaldehyde-based resin mixed with specific additives, a specially designed catalyst is formed to obtain a material having properties suitable for use as a mining blasthole plug.

[0059] The material constituting the burst plug of the present invention is formed of a two-component composition or mixture comprising a formaldehyde-based resin and a catalyst suitable for the resin.

[0060] The resin used as the material for forming the plug is synthesized based on formaldehyde and another comonomer that is capable of forming a stable copolymer with formaldehyde and has properties suitable for the desired use. Such comonomers may be selected from (but not limited to) phenol, urea, melamine, resorcinol, etc. In addition, semi-polymeric materials such as pMDI (polymethyl diisocyanate) or any block of petroleum-based materials capable of reacting with formaldehyde may be used. In addition, renewable materials such as tannin, lignin or any other lignocellulosic material capable of copolymerizing with formaldehyde may be used.

[0061] The above copolymers may also be used as blends. The formaldehyde based polymers may be used in different molar ratios, with various sizes and degrees of polymerization, viscosities, pH conditions and total solids contents suitable for use as plug materials.

[0062] The mentioned resin composition may contain other types of substances which combine the desired properties into the material to be used as a plug, such as (but not limited to):

[0063] - Rheology modifiers that provide special flow or rheological properties, such as acrylic polymers or prepolymers, polyurethanes, carbohydrates, lignocellulosic materials, etc.;

[0064] - Surfactants that impart defoaming or foaming properties to the material;

[0065] - a buffer or pH regulator suitable for the coagulation material; the buffer may be inorganic or organic;

[0066] - a gasifying agent, such as pentane, hexane, dichloromethane or any other additive that generates a gas during the solidification reaction of the material used as the plug;

[0067] - Expanding agents, such as carbonates or polycarbonates, organic solvents miscible with phenolic resins, melamine resins (MUF) or PRF with a chain length not exceeding 6 carbons.

[0068] The above resins are reacted with a catalyst, which depends on the type of resin used.

[0069] The type of resin is considered when selecting the catalyst, so acidic, basic, or cross-linker-based catalysts may be used to produce a material suitable for use as a stopper.

[0070] The acidic catalyst may be selected from, but not limited to, inorganic acids such as sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, or mixtures thereof. The catalyst may also be selected from organic acids such as formic acid, lactic acid, benzenesulfonic acid derivatives, citric acid, acetic acid, or mixtures thereof. As previously mentioned, the acid may be used in the mixture in a proportion suitable for the setting reaction of the resin used.

[0071] The basic catalyst may be selected from, but not limited to, an inorganic base such as potassium hydroxide, barium hydroxide, sodium hydroxide, calcium hydroxide or a mixture thereof. The catalyst may also be selected from an organic base such as diethylamine, triethylamine, ethanolamine or a mixture thereof. As previously mentioned, the acid and base may be used in the mixture in a ratio suitable for the coagulation reaction of the resin used.

[0072] The catalyst based on the cross-linking agent or hardening agent can be selected from (but not limited to) pMDI, erythritol and its derivatives, polyols, acrylic resins, polyvinyl alcohol, formaldehyde, succinic acid derivatives, alkaline formaldehyde (such as ), glycidol and epoxide derivatives, or mixtures thereof, or any difunctional or polyfunctional compound capable of hardening the above resins. Each of these components or mixtures thereof may be used in conjunction with one or more of the acidic or basic catalysts mentioned in the preceding paragraphs.

[0073] The catalyst may consist of one or more of the above mentioned reagents.

[0074] The weight ratio of resin to catalyst in the two-component mixture (resin / catalyst) is in the range from 9:1 to 1:9; preferably from 3:1 to 1:3. Depending on the type of system and catalyst used, this ratio can even be 2:1 to 1:2, in this way producing hardnesses of 1 to 10 N / mm 2 of rigid foam material.

[0075] In particular, the two-component composition or mixture of the present invention is constructed from a phenol-formaldehyde (PF) resin or a melamine-urea-formaldehyde (MUF) resin, the proportion of the resin components being 50±20% by weight, which means that the proportion of one component is 30% to 70% and the proportion of the other resin component is 70% to 30%. The resin mixture is preferably reacted in situ, i.e. in the same blast hole, with a catalyst in a proportion of 50±20% of the total weight of the mixture, the additives being used in the desired proportions.

[0076] Example

[0077] Embodiment 1:

[0078] Laboratory scale plugs were constructed in order to demonstrate the physicochemical and mechanical properties of the two-component mixture of resin and catalyst of the present invention compared to plugs produced with the components used in the prior art.

[0079] Plugs formed from the following resins were tested:

[0080] PF: phenolic resin, molar ratio is 1.6 (the present invention);

[0081] PUR: polyurethane resin (comparative);

[0082] pMDI: polymethyl diisocyanate (comparative);

[0083] pMDI-LS: Low Reactivity Polymethyl Diisocyanate (comparative);

[0084] PRF: formaldehyde resin / (resorcinol+phenol), molar ratio of 0.8 to 1.0 (present invention);

[0085] MUF-1: formaldehyde resin / (melamine+urea), molar ratio of 1.2 to 1.8 (low viscosity) (the present invention);

[0086] MUF-2: formaldehyde resin / (melamine+urea), molar ratio of 1.2 to 1.8 (high viscosity) (invention).

[0087] Table 1 describes the two-component mixture of the resin and catalyst of the present invention and the foam produced with a commercial resin as a comparison, and Table 2 shows the composition of the catalyst used.

[0088] Table 1 : Composition of foams produced with resins and catalysts according to the invention and other commercially available foams as comparison.

[0089]

[0090] Table 2: Catalysts used to form the two-component mixtures of Table 1.

[0091]

[0092] The tests were carried out in transparent polycarbonate tubes 40 cm in length and 10 cm in diameter. These tubes were filled with gravel to a height of 22 cm and 300 g of a mixture of resin and catalyst were poured onto the gravel. Figure 1 shown.

[0093] Measurements were made to record the extent of diffusion of the two-component mixture in the gravel, the setting time, the degree of expansion, and the maximum temperature reached by the mixture at the surface and bottom.

[0094] Table 3 shows a summary of the average results obtained from the various laboratory tests. Column numbers 1 to 7 are Figure 1 The numbers in the photos correspond.

[0095] Table 3: Summary of results obtained from laboratory tests.

[0096]

[0097] As can be seen from the results shown in Table 3, the expansion and volume change parameters of the formed resin allow the plug formation to be controlled so that it can be extrapolated to the blast hole and not exceed the volume limits that the hole can accommodate when the plug is formed.

[0098] It may also be appreciated that the setting time of the two-component mixture of the present invention is much shorter than the time for forming rigid foam with the other resins tested.

[0099] When the resin and catalyst reacted to form the plug, the temperature change with time was measured, e.g. Figure 2 As shown, it is found here that the bottom temperature remains constant, except for the pMDI mixture (above 100°C, comparative). It can therefore be determined that the composition of the invention has the advantage of maintaining a temperature equal to or below 40°C, which is beneficial for the detonation operation, since detonating cords have limitations and safety standards and cannot be operated at temperatures above 55°C, since above this temperature they may malfunction, possibly preventing proper detonation and creating all the problems associated with so-called "misfires", which means a dangerous situation in the mine due to potential explosives. Therefore, an exothermic temperature below 40°C is a very ideal condition.

[0100] Embodiment 2:

[0101] The physicochemical properties of the experimental formulations of Example 1 were optimized on a laboratory scale to produce stable compounds for in situ blasting with explosive materials to verify the feasibility and scalability of the prototype.

[0102] The test of the present invention was conducted to evaluate the method of forming a burst plug of the present invention with a formaldehyde-based resin and a catalyst which react and produce a rigid foam when applied in situ, i.e., on site. The test included a comparison with a conventional plug.

[0103] The mixture of formaldehyde resin and catalyst is directly loaded into the hole in the required amount (i.e., 2 to 100 kg) taking into account that the expansion volume is 3 to 5 times the loading volume of the mixture, depending on the diameter and depth of the hole. The time required for loading the hole is about 30 seconds to 5 minutes, depending on the loading volume, and the foam formation time is about 3 to 10 minutes, which also depends on the loading volume.

[0104] For the field examples, holes with plugs based on the phenolic resin-catalyst two-component mixture of the present invention and conventional holes with drill cuttings were considered. Drill cuttings refers to ground material obtained by drilling ore during hole construction, used as the only component of the conventional plug. The hole with the plug of the present invention has a proportionally minimum fraction of drill cuttings in its design.

[0105] The perforation design, loading configuration and detonation were kept constant. Table 4 shows the drilling and blasting design parameters for the blast holes.

[0106] Table 4: Drilling and blasting design parameters

[0107]

[0108] Figure 3 Represents the scheme for the construction and design of blastholes according to the parameters defined in the table above.

[0109] Figure 4 A flow chart showing a preferred embodiment of a method of applying a two-component mixture of resin and catalyst of the present invention mounted on a truck to allow mobility of the system.

[0110] The application system comprises a first tank containing the resin and a second tank containing the catalyst. In a preferred embodiment, the volume of these tanks is about 1 m 3 .

[0111] The first flow starts from the first tank and flows to the first pump. The first pump can be a screw pump or a centrifugal pump, for example driven by a motor powered by a generator. The first tank can also include an internal mechanical stirrer for homogenization and recirculation of the resin, and a heater to maintain the necessary temperature under low ambient temperature conditions. Alternatively, the second tank can also include such a feature ( Figure 4 not shown).

[0112] The second flow starts from the second tank by a second pump. The second pump may be a pneumatic pump, for example driven by a compressor, which is also powered by a generator.

[0113] Both streams were standardized to a predetermined ratio of 3:1 to 1:3 (resin to catalyst).

[0114] like Figure 4 As shown, the first and second streams are directed through various valves to a mixer, such as a static mixer, to achieve homogenization of the catalyst and resin. Once the mixture has been mixed, the mixture is deposited directly into the blast hole.

[0115] Figure 4 Also shown is a preferred embodiment of the application method with various valves that open or close the flow path. In the event that the pressure is high enough and / or other valves are closed, both the first and second flows can be redirected to their respective pools by, for example, a pressure relief valve.

[0116] The compressor is additionally used to provide an air flow when the system is stopped or the application of the mixture is terminated. This air flow can clean the pipeline and in particular avoid residues of the homogenized and solidified mixture from being deposited in the static mixer.

[0117] The first and second flows and the air flow may be adjusted manually by reading various mass flow meters, or automatically by a programmable logic controller (PLC).

[0118] Considering that the foam forming volume will expand 3 to 5 times, the amount of the mixture of resin and catalyst to be loaded into the hole is calculated according to the diameter and height of the blasting hole. The filling time of one hole is about 30 seconds to 1 minute and the foaming time is about 40 to 60 seconds.

[0119] The mixer used in the test corresponds to a static mixer 30 cm long and 1 inch (2.54 cm) wide, with a flow rate design range of 1 to 200 L / min.

[0120] The procedure for forming a plug with the rigid foam of the present invention and then detonating and bursting it comprises the following steps:

[0121] - Loading explosives i.e. 28.7 kg of ANFO (Ammonium Nitrate-Fuel Oil) to the bottom of each hole,

[0122] - loading of a layer of drill cuttings or stones (1-2 kg of material, equivalent to 0.5 m) to seal and prevent the foam of the invention from coming into contact with the explosives,

[0123] - 3.5 kg of the foam according to the invention are introduced in a period of 30 seconds to 1 minute according to the above method,

[0124] - The foam according to the invention is allowed to set, which lasts from 1 to 3 minutes.

[0125] -Once the hole filling operation is completed, the area is evacuated and the hole is detonated.

[0126] For comparison, 2 meters of drill cuttings were loaded in conventional holes without using the foam of the invention. The filling time of these conventional holes was 5 minutes on average.

[0127] After detonation, air pressure measurements and aerial camera inspections were conducted to determine dust emissions and plume height.

[0128] The total reaction time for the rigid foam of the present invention to solidify, i.e., the time for the rigid foam to reach the final hardness, is 1 to 3 minutes. Therefore, the reaction is completed very quickly, which provides efficient performance in terms of loading plugs and explosives in blasting areas.

[0129] The density of the obtained foam is about 0.25 g / m 3 , its stiffness is about 2N / mm 2 These values ​​obtained from the foam improve the blasting performance, allowing more noise and greater energy expansion to be retained upon detonation, and also allowing a higher degree of rock fragmentation, compared to conventional holes.

[0130] The test conducted on site showed that the maximum heat release occurred at 6.5 seconds, and the maximum temperature on the foam surface reached 40.6°C. Figure 5 As shown, it is safe and can keep the wires in good condition and not be damaged by temperature.

[0131] By recording images using slow motion at 240 frames per second, the retention time of the detonation and the ejection height can be obtained. The retention time is also called the detonation velocity and corresponds to the speed at which the shock wave travels forward through the detonated explosive.

[0132] The recorded images prove that the tests conducted on site allowed the use of a plug formed from the phenolic resin of the present invention to seal the gas within the blasting hole, with an injection delay of 50 milliseconds relative to the detonation start point marked by the electronic system in a conventional hole without foam, and the injection height of the conventional plug was 15 meters, while the injection height of the plug of the present invention was reduced to 5 meters.

[0133] Figure 6 Shown are photos taken at the same comparative time when blasting with and without the plug of the present invention. The photos of the upper picture (conventional blasting) and the lower picture (blasting with the resin plug of the present invention) were taken with a drone at 0, 30 and 50 milliseconds during operation.

[0134] In addition to the heights measured in both cases, during the blasting, dense smoke and dust are clearly observed in the upper photo, while in the lower photo, less dense smoke can be seen and there are even blasting sections where no dust is ejected from the blasting hole.

[0135] On the other hand, blasting with the plug of the present invention produces a more fragmented blast zone compared to conventional blasting plugs, where the rock size is reduced by 30-50% relative to conventional blasting.

[0136] The reduction in air pressure was also measured and mathematically related by software to the intensity of sound during the blast, resulting in a 50% to 90% reduction in decibels compared to conventional blasting.

[0137] To determine the behavior of the explosive and the decibel measurements, two conventional blasts were considered, where the configuration of the blast hole design was the same as defined in this example. Likewise, three blasting operations were performed under the same conditions using the plug of the invention and compared with the noise behavior of the conventional plug. Table 5 provides a summary of the measurements obtained.

[0138] Table 5: Results of field tests to determine the noise reduction of plugs loaded with the two-component mixture of the invention (PF+catalyst) in blasting, compared with plugs loaded with drill cuttings in conventional blasting.

[0139]

[0140]

Claims

1. A method for forming a mining blast hole plug, characterized in that: The method comprises the following steps: - loading a two-component mixture of resin and catalyst onto explosives separated by a layer of drill cuttings in a blast hole, said two-component mixture forming a foam in situ in said hole; - allowing the foam to solidify to form a hard foam, Once the two-component mixture solidifies, detonation occurs.

2. The method for forming a blast hole plug according to claim 1, characterized in that: The resin in the two-component mixture is a formaldehyde-based resin.

3. The method for forming a blast hole plug according to claim 2, characterized in that: The formaldehyde-based resin is selected from phenol-formaldehyde (PF) resin, urea-formaldehyde (UF) resin, melamine-formaldehyde (MF) resin, melamine-urea-formaldehyde (MUF) resin, phenol-resorcinol-formaldehyde (PRF) resin, formaldehyde-based resin modified with lignin or tannin, and derivatives thereof.

4. The method for forming a blast hole plug according to claim 1, characterized in that: The catalyst in the two-component mixture is selected from an acidic catalyst, a basic catalyst or a catalyst based on a crosslinker.

5. The method for forming a blast hole plug according to claim 4, characterized in that: The acid catalyst is selected from inorganic acids such as sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid or mixtures thereof; organic acids such as formic acid, lactic acid, benzenesulfonic acid derivatives, citric acid, acetic acid or mixtures thereof.

6. The method for forming a blast hole plug according to claim 4, characterized in that: The basic catalyst is selected from inorganic bases such as potassium hydroxide, barium hydroxide, sodium hydroxide, calcium hydroxide or mixtures thereof; and organic bases such as diethylamine, triethylamine, ethanolamine or mixtures thereof.

7. The method of forming a blast hole plug according to claim 4, characterized in that: The crosslinking agent or hardener based catalyst is selected from polymethyl diisocyanate (pMDI), erythritol and its derivatives, polyols, acrylic resins, polyvinyl alcohol, formaldehyde, succinic acid derivatives, alkaline formaldehyde such as Glycidol and epoxide derivatives, or mixtures thereof.

8. The method of forming a blast hole plug according to claim 1, characterized in that: The weight ratio of resin to catalyst is in the range of 9:1 to 1:9, preferably 3:1 to 1:3, more preferably 2:1 to 1:

2.

9. A method of forming a blast hole plug according to any one of the preceding claims, characterised in that: The method also includes optionally applying other additives such as rheology modifiers, surfactants, buffers or pH adjusters, gasifying agents, bulking agents.

10. A system for forming a mining blast hole plug to perform the method of claim 1, characterized in that The system allows the in-situ formation of rigid foam blocks using a two-component mixture of resin and catalyst, the system comprising - a first tank containing said resin, - a second cell containing said catalyst, - a mixer-applicator for homogenizing and applying the two-component mixture, - pumps and valves allowing the plug to be loaded into said blast hole, - Monitoring system.

11. A mixture for use as a blasting plug in a mining blast hole, characterized in that It comprises a two-component mixture of a resin and a catalyst, wherein the resin is formaldehyde-based.

12. The mixture according to claim 11, characterized in that The formaldehyde-based resin is selected from phenol-formaldehyde (PF) resin, urea-formaldehyde (UF) resin, melamine-formaldehyde (MF) resin, melamine-urea-formaldehyde (MUF) resin, phenol-resorcinol-formaldehyde (PRF) resin, formaldehyde-based resin modified with lignin or tannin, and derivatives thereof.

13. The mixture according to claim 11, characterized in that The catalyst in the two-component mixture is selected from an acidic catalyst, a basic catalyst or a catalyst based on a crosslinker.

14. The mixture according to claim 13, characterized in that The acid catalyst is selected from inorganic acids such as sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid or mixtures thereof; organic acids such as formic acid, lactic acid, benzenesulfonic acid derivatives, citric acid, acetic acid or mixtures thereof.

15. The mixture according to claim 13, characterized in that The basic catalyst is selected from inorganic bases such as potassium hydroxide, barium hydroxide, sodium hydroxide, calcium hydroxide or mixtures thereof; and organic bases such as diethylamine, triethylamine, ethanolamine or mixtures thereof.

16. The mixture according to claim 13, characterized in that The crosslinking agent or hardener based catalyst is selected from polymethyl diisocyanate (pMDI), erythritol and its derivatives, polyols, acrylic resins, polyvinyl alcohol, formaldehyde, succinic acid derivatives, alkaline formaldehyde such as Glycidol and epoxide derivatives, or mixtures thereof.

17. The mixture according to claim 11, characterized in that The weight ratio of resin to catalyst is in the range of 9:1 to 1:9, preferably 3:1 to 1:3, more preferably 2:1 to 1:

2.

18. The mixture according to any one of claims 11 to 17, characterized in that The mixture also includes the optional application of other additives such as rheology modifiers, surfactants, buffers or pH adjusters, gasifying agents, bulking agents.

19. Use of a two-component mixture of resin and catalyst according to claims 11 to 18, characterized in that The two-component composition is used to form blast plugs in mining blast holes to reduce plug loading time, increase rock fragmentation, reduce blast noise and contain particulate matter generated by the blast.

20. A method of loading and blasting a mining blast hole, characterized in that The method comprises the following steps: - installing explosives in said blast holes, - adding a layer of drill cuttings on said explosive, - loading a two-component mixture of resin and catalyst on the drill cuttings layer, - Allow the foam to solidify, - detonating said explosive, wherein the drill cuttings layer acts as a separation medium between the explosive and the two-component mixture, preventing the mixture from diffusing into the explosive, and The two-component mixture forms a rigid foam in situ, generating an expanded volume of 3 to 5 times the loading volume of the mixture.

Citation Information

Patent Citations

  • Packaging for antimicrobial treatment of plants comprising particulate material, natural oil and an antagonist of a microbial pathogen.

    CL201503059

  • Method for plugging a perforation of a borehole, which comprises pumping a superabsorbent polymer gel that has at least 25:1 of its own weight in water into a perforation of a borehole loaded with an explosive; and a borehole perforation arrangement that comprises an explosive and a polymer gel.

    CL201503656

  • retaining plug for blast holes

    CL201701076

  • Composition and method for blast hole loading

    EP3132205A1

  • Borehole plug and method.

    ES8800739A1